Air pollution abatement performances of green infrastructure in open road and built-up street canyon environments – A review. (August 2017) - Abhijith, K.V.; Kumar, Prashant; Gallagher, John; McNabola, Aonghus; Baldauf, Richard; Pilla, Francesco; Broderick, Brian; Di Sabatino, Silvana; Pulvirenti, Beatrice
Abstract: Intensifying the proportion of urban green infrastructure has been considered as one of the remedies for air pollution levels in cities, yet the impact of numerous vegetation types deployed in different built environments has to be fully synthesised and quantified. This review examined published literature on neighbourhood air quality modifications by green interventions. Studies were evaluated that discussed personal exposure to local sources of air pollution under the presence of vegetation in open road and built-up street canyon environments. Further, we critically evaluated the available literature to provide a better understanding of the interactions between vegetation and surrounding built-up environments and ascertain means of reducing local air pollution exposure using green infrastructure. The net effects of vegetation in each built-up environment are also summarised and possible recommendations for the future design of green infrastructure are proposed. In a street canyon environment, high-level vegetation canopies (trees) led to a deterioration in air quality, while low-level green infrastructure (hedges) improved air quality conditions. For open road conditions, wide, low porosity and tall vegetation leads to downwind pollutant reductions while gaps and high porosity vegetation could lead to no improvement or even deteriorated air quality. The review considers that generic recommendations can be provided for vegetation barriers in open road conditions. Green walls and roofs on building envelopes can also be used as effective air pollution abatement measures. The critical evaluation of the fundamental concepts and the amalgamation of key technical features of past studies by this review could assist urban planners to design and implement green infrastructures in the built environment. Graphical abstract: Highlights: Green infrastructure can play a significant role in mitigating urban air pollution. Air quality changes in local built environments due to vegetation are assessed. Low-level hedges improves air quality in street canyons unlike high-level trees. Green green walls and roofs are effective to reduce pollution in streets/open roads. Prior design of green infrastructure should be performed for improving air quality.